Perancangan Model Arsitektur Sistem Informasi Monitoring Keuangan Warga Menggunakan Enterprise Architecture Planning - Andhika Pratama Hakim; Sawali Wahyu (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Graha Pesona Housing is a housing complex located in Citra Raya. Graha Pesona housing has community units (RW) and neighborhood units (RT) which serve residents in various matters regarding housing needs. Every resident in Graha Pesona Housing is required to pay a citizen fee. Some business processes at Graha Pesona Housing do not run according to business functions. The current problem is that the system is not integrated where the recording and collection of residents' dues is still done manually where the RT management will go to the residents' houses one by one. Until the benefits of a structured, integrated, and planned information system are obtained. Enterprise Architecture Planning (EAP) can support architectural design at Graha Pesona Housing, EAP which aims to provide an integrated and efficient information system based on needs. The EAP (Enterprise Architecture Planning) methodology is an architectural modeling method developed to build enterprise architecture. This enterprise architecture modeling creates a blueprint consisting of application architecture, technology architecture, and data architecture that can be used as a reference for changes and development of information systems at Graha Pesona Housing to support its business functions.